Interactive learning: advantages and disadvantages - Kustovska, O.; Svidenyuk, A. (Land Management, Cadastre and Land Monitoring, 2017)
In the article the use of interactive technologies in the educational process of the university, allowing students to develop innovative thinking, away from stereotypes, develop imagination, communication skills and expertise, intellectual, emotional, motivational and other areas of personality. Implementing the principles of technological learning, interactive educational technology and provides interactive computer learning tools, and interactivity of educational process when the basic conceptual provisions defined training based on interactive communication. Key words: interactive learning technology, teacher, students, innovative thinking, communication skills.